Online kinship. Social media as a site for challenging notions of gender and family. - Andreassen, Rikke (MedieKultur: Journal of media and communication research, 2016)
The article shows how the technology of social media sites facilitates new kinds of kinship. It ana-lyzes how ‘donor families’ – i.e., families in which the children are conceived via sperm and/or egg donations – negotiate kinship, family formations and gender when connecting with each other online. Family formation and parenting are closely connected with gender and gender norms, and online donor families, therefore, offer an opportunity for understanding gender and gender for-mations in contemporary times and contemporary media. By analyzing commentary threads of a Facebook group connecting donor families as well as interviews with users of this Facebook group, the article shows how the affordances of social media, especially the Facebook application for smart phones, are central to the formation and maintenance of new kinship relations. Furthermore, the article illustrates how conventional practices regarding gender and families on one hand are chal-lenged by the creation of new types of families, while simultaneously being maintained in discus-sions about choice of donor. Here, a longing for traditional family values seems to run underneath the discussion between members of these new families.